THE LIMITS OF DIGITALISING STATE ENVIRONMENTAL ADMINISTRATION - ZASLAVSKAYA Nadezhda Mikhailovna (Правовое государство: теория и практика)
The article considers the legal aspects of the digitalisation of certain functions of state environmental management. The relevance of the chosen research topic is conditioned by such national development goals of the Russian Federation as «environmental well-being» and «digital transformation of state and municipal administration, economy and social sphere». Purpose: to determine the limits of digitalisation as a guarantee of the effectiveness of state environmental administration. Methods: search and collection of data, their processing: description, generalisation, classification, search for patterns; analysis of the results of data processing. The article concludes that not all areas of state environmental administration activities and not everything should be digitalised for the purposes of its effective (efficient) implementation.